Toward an international measure of global competence? A critical look at the PISA 2018 framework. (15th March 2019) - Engel, Laura C.; Rutkowski, David; Thompson, Greg
ABSTRACT: This paper focuses on the OECD's PISA 2018 international framework for global competence. Given the growing national and international attention on educating for global competence, and absent of other measures, there is a need to scrutinise this framework. Our critical analysis is conceptually framed by academic literature related to (a) the OECD's influential role in facilitating neoliberal education policy trends, (b) disjuncture and debate surrounding global competence, and (c) how influence is garnered through measurement technologies. We conclude by encouraging the OECD to be transparent in the reporting of results and educational stakeholders to be cautious interpreters of forthcoming results and rankings.